Study of Groundwater Feasibility in Residential Settlements Near the Former Final Waste Disposal Place, Kutaraja District, Banda Aceh City - Mice Putri Afriyani; Muttakin Muttakin; Aulia Margareta Prakatiwi; Puspita Annaba Kamil (Jurnal Ilmu Lingkungan, 2025)
As the population increases, the amount of water needed increases. Banda Aceh needs more clean water every year. The total needs range from 130-150 liters/person/day. The research was carried out at the Kutaraja department. The purpose of the research is to examine the properties of groundwater around the former final drainage site. The research was carried out through field surveys that included measurements of the geographical coordinates of the well location using a sampling grid according to the physical parameters of freatic soil water. The results of the ground water in Kutaraja district on the freatic ground water temperature parameter are a maximum of 35 °C and a minimum of 28 °C. Results Physical parameters such as smell, color, and flavor still meet the requirements. TDS parameters, with the highest TDS value of 12020 mg/l. The measured pH of the groundwater obtained still qualifies for groundwater quality.